(untitled) (International Journal of Physiotherapy, 2018)
Background: This review summarizes the evidence regarding the association between musculoskeletal disorders and computer users at work. Past studies had identified that musculoskeletal disorders among computer users are known to be multifactorial in origin. This includes work related and nonwork-related factors. Methods: Literature search was conducted in various databases such as Pubmed, ScienceDirect, and Scopus. The articles were analyzed based on predetermined objectives and Medical Subject Headings (MeSH) such as computer users, musculoskeletal disorders and risk factors. Almost seventy-seven (77) articles were retrieved and analyzed to understand the occurrence of musculoskeletal disorders among computer users. Results: Based on the previous articles, a framework of musculoskeletal disorders and computer users was proposed for a better understanding of the occurrence of musculoskeletal disorders among computer users in the workplace. The framework emphasizes the association between work-related (physical, environmental and psychosocial risk factors) and non-work related factors (individual risk factors) among computer users. It was hypothesized that an increase in the muscle activity or increase in the muscle loads were the possible early symptoms of musculoskeletal disorders among computer users at the workplace due the interaction of individual, psychosocial and physical risk factors. Furthermore, the decrease in productivity was shown in the framework as an effect of an increase in musculoskeletal disorders among computer users. Conclusion: The proposed framework may be used for better prevention and intervention of musculoskeletal disorders among computer users in the workplace.